Stereotactic body radiation combined with oncolytic vaccinia virus induces potent anti-tumor effect by triggering tumor cell necroptosis and DAMPs. (28th December 2021) - Chen, Wan-Yu; Chen, Yu-Li; Lin, Han-Wei; Chang, Chi-Fang; Huang, Bing-Shen; Sun, Wei-Zen; Cheng, Wen-Fang
Abstract: Radiation is an integral part of cancer therapy. With the emergence of oncolytic vaccinia virus immunotherapy, it is important to study the combination of radiation and vaccinia virus in cancer therapy. In this study, we investigated the anti-tumor effect of and immune mechanisms underlying the combination of high-dose hypofractionated stereotactic body radiotherapy (SBRT) and oncolytic vaccinia virus in preclinical murine models. The combination enhanced the in vivo anti-tumor effect and increased the numbers of splenic CD4 + Ki-67 + helper T lymphocytes and CD8 + Ki-67 + cytotoxic T lymphocytes. Combinational therapy also increased tumor-infiltrating CD3 + CD4 + helper T lymphocytes and CD3 + CD8 + cytotoxic T lymphocytes, but decreased tumor-infiltrating regulatory T cells. In addition, SBRT combined with oncolytic vaccinia virus enhanced in vitro cell death, partly through necroptosis, and subsequent release of damage-associated molecular patterns (DAMPs), and shifted the macrophage M1/M2 ratio. We concluded that SBRT combined with oncolytic vaccinia virus can trigger tumor cell necroptosis and modify macrophages through the release of DAMPs, and then generate potent anti-tumor immunity and effects. Thus, combined therapy is potentially an important strategy for clinical cancer therapy. Highlights: Stereotactic body radiation with oncolytic vaccinia generates potent anti-tumor immunity and effects. Radiation combined with oncolytic vaccinia increases the immune responses of both helper and cytotoxic T lymphocytes. Radiation combined with oncolytic vaccinia triggers tumor cell necroptosis. Radiation combined with oncolytic vaccinia modifies macrophages through the release of DAMPs.